The Small Words of Film Spoken Language for Second Language Learning - GIAMPIERI, PATRIZIA (International Journal of Language, Translation and Intercultural Communication, 2019)
Although being scripted, film dialogues are claimed to mirror natural spoken language. Exposing second language (L2) learners to instances of authentic language is reported to be stimulating and enjoyable. Amongst others, natural spoken discourse is hallmarked by discourse markers, which are small words, or prefabricated units, which constitute the bulk of native-like conversation. Helping students become acquainted with the small words of natural language can increase their perceived proficiency. In light of these argumentations, this paper is aimed at presenting a trial lesson with sixteen young adults who participated in a 2-hour class. During the class, they became acquainted with discourse markers, which were sourced from film dialogues. Students had firstly to infer their meanings and propose coherent translation candidates by recurring to their interlanguage. Then, they were prompted to search for translations in online language platforms. The paper findings highlight that the trial lesson was not only enjoyable and stimulating, but students felt that their L2 knowledge increased. Furthermore, they were stimulated by the inferring tasks and appreciated the word search. In some instances, students' inferences outperformed dictionary results and online suggestions.